catena-Poly[[[diaquabis(1H-indole-3-acetato-κO)cobalt(II)]-μ-4,4′-bipyridine-κ2N:N′] tetrahydrate] - Seik Weng Ng (Acta Crystallographica Section E, 2008)
The 4,4′-bipyridine spacer in the title compound, [Co(C10H8NO2)2(C10H8N2)(H2O)2]·4H2O, links the diaquacobalt(II) dicarboxylate units into a linear chain; the metal atom lies on a center of inversion in an octahedral environment. The coordinated and uncoordinated water molecules interact through O—H...O hydrogen bonds to form a three-dimensional network.